(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
This article addresses the 2017 reform to the Commercial Code, regarding the commercial oral trial, regarding the relief of the expert evidence, because, since this procedure was implemented on January 27, 2011 (DOF), it indicated that the expert evidence to be admitted in the preliminary hearing, a period of 10 days would be granted to present the opinion and if those exhibited by the experts of the parties are contradictory, a third-party expert in disagreement would be appointed, who would present his opinion in the trial hearing and in this hearing the expert evidence was relieved, with the opinions of the experts of the parties and of the third party in disagreement; However, according to the reform indicated, the experts of the parties must present their opinion at the trial hearing and if they are contradictory, the third expert in disagreement will be appointed at that hearing and their opinion will be exhibited at a later hearing; therefore, said reform prolongs the commercial oral trial to a third hearing, contravening the speed for which this procedure was created; In addition, the principles of concentration and continuity, which are intertwined, indicate that all disputed issues must be resolved and raised before the same Judge to be resolved in a single hearing if possible, hence, a new reform that harmonizes with the fluidity of this procedure.